ChemInform Abstract: One‐Step Synthesis of a [20]Silafullerane with an Endohedral Chloride Ion. Issue 28 (25th June 2015) - Tillmann, Jan; Wender, Josef Heinrich; Bahr, Ute; Bolte, Michael; Lerner, Hans‐Wolfram; Holthausen, Max C.; Wagner, Matthias
Abstract Discrete Si20 dodecahedra stabilized by an endohedral guest and valence saturation are prepared by a Cl‐‐induced disproportionation of Si2Cl6 in the presence of Bu3N.